Analisis Faktor-Faktor yang Mempengaruhi Pemilihan Metode Penilaian Persediaan pada Perusahaan Dagang yang Terdaftar di Bursa Efek Indonesia Periode 2010-2014 - Riswan RISWAN; Restiani Fasa (Universitas Bandar Lampung (UBL), 2016)
This study aimed to determine the effect of financial leverage, firm size, managerial ownership,and current ratio for the selection of inventory valuation methods in trading companies listed in Indonesia Stock Exchange period 2010-2014 . The sample in this study is the trading companies listed in Indonesia Stock Exchange period 2010-2014. Sampling technique used in this study is purposive sampling, so that obtained 19 companies. The data in this research is secondary data derived from the Indonesian Capital Market Directory (ICMD) and historical data from the company's website by downloading in IDX. This study uses quantitative analysis, using dummy variables and hypothesis testing using logistic regression. The results showed that financial leverage significantly influence the selection of inventory valuation methods, firm size, managerial ownership,and current ratio has no significantly effect on the selection method of inventory valuation. The best inventory valuation methods is Average Method in trading companies listed in Indonesia Stock Exchange period 2010-2014 .